Efektivitas Pijat Loving Armet Laktasi Terhadap Volume Asi dan Intensitas Nyeri pada Payudara - Endah Wahyutri; Kusmini Suprihatin; Jasmawati Jasmawati; Rosalin Ariefah Putri (Husada Mahakam, 2021)
Breastfeeding is the process of giving milk to a baby or small child with breast milk from the mother's breast. Let down reflex (reflex release of the hormone prolactin for milk production and oxytocin) for milk flow can be smooth. Another effect is an increase in Haemoglobin levels. This study aims to analyze the effect of Loving Armet Lactation Massage on the smooth production of breast milk, breast pain. This research was conducted on breastfeeding mothers in the first week of delivery with marmet massage and oxytocin as control and Loving Armet Lactation Massage as treatment. The research method used in this study was a queasy experimental design with a non-equivalent control group pre-post test design, the number of respondents was 15 cases and 15 controls. The massage was carried out on the 7th day postpartum. The results of the study there was an increase in milk production in both cases and controls, there was no difference in marmet massage, P-value 0.52, and there was a difference in cases with a P-value of 0.000. Pain reduction occurs in marmet massage and Loving Armet massage. level of 0.910. Conclusion Loving Armet massage is effective in increasing breast milk production, reducing breast pain. Loving Armet massage advice is applied in service settings and is an entrepreneurial opportunity.